Anesthesia management for transapical transcatheter aortic valve implantation: a case series - Fassl, Jens; Walther, Thomas; Groesdonk, Heinrich Volker; Kempfert, Joerg; Borger, Michael Andrew; Scholz, Markus; Mukherjee, Chirojit; Linke, Axel; Schuler, Gerhard; Mohr, Friedrich Wilhelm; Ender, Joerg (Journal of cardiothoracic and vascular anesthesia, 2009)
OBJECTIVE\backslashr\backslashnThe purpose of this study was to review the management of anesthesia for transapical transcatheter aortic valve implantation.\backslashr\backslashnDESIGN\backslashr\backslashnRetrospective review of collected data.\backslashr\backslashnSETTING\backslashr\backslashnUniversity-affiliated heart center.\backslashr\backslashnPARTICIPANTS\backslashr\backslashnOne hundred consecutive patients with severe aortic stenosis.\backslashr\backslashnINTERVENTIONS\backslashr\backslashnGeneral anesthesia followed by an established fast-track protocol.\backslashr\backslashnMATERIALS AND METHODS\backslashr\backslashnA total of 100 patients with significant AS received transapical transcatheter aortic valve implantation. The patients were treated following a fast-track protocol. The mean arterial pressure was maintained above 65 mmHg by volume and/or inotropes during the procedure. The mean arterial pressure was increased above 75 mmHg to avoid hemodynamic deterioration before starting rapid ventricular pacing for the balloon valvuloplasty and the valve implantation. Transesophageal echocardiography was used to assess valve size and for hemodynamic monitoring. Eighty-one patients were treated completely off pump. There was a significant decline in mean arterial pressure from pre- to postvalvuloplasty (74.7 +/- 9.1 mmHg v 63.6 +/- 11.3 mmHg, p < 0.001) and from pre- to postimplantation (76.5 +/- 12.6 mmHg v 67.2 +/- 12.7, p < 0.001). The first 10 patients in the study intentionally were placed on cardiopulmonary bypass, and 9 patients required cardiopulmonary bypass because of hemodynamic deterioration.\backslashr\backslashnCONCLUSION\backslashr\backslashnA well-designed anesthetic plan as well as an understanding of the surgical procedure and the hemodynamic effects of rapid ventricular pacing are required to ensure successful outcomes in this new surgical option for high-risk patients.